A Study of Deviance as a Retaliatory Response to Organizational Power - Sims, Randi L. (Journal of business ethics, 2010)
In a time when ethical scandals are commonplace in the media, one begins to wonder just what organizations are doing wrong. This article analyzes the Fall 2006 boardroom spying scandal at Hewlett–Packard to determine whether the workplace deviance observed can be linked to a retaliatory response to organizational power. A summary of the events leading up to, during, and the fall-out of the scandal is reported.